111k views
0 votes
2(5m-8)+3(m+2)=12+4(2m-1)

2 Answers

6 votes
  • Answer:

m = 3 3/5

  • Explanation:

Hi there !

2(5m - 8) + 3(m + 2) = 12 + 4(2m - 1)

10m - 16 + 3m + 6 = 12 + 8m - 4

10m + 3m - 8m = 12 - 4 + 16 - 6

5m = 18

m = 18/5

m = 3 3/5

Good luck !

User Peter Wessberg
by
5.3k points
2 votes

Answer:

3.6

Explanation:

2(5m-8)+3(m+2)=12+4(2m-1)

10m - 16 + 3m + 6 = 12 + 8m -4

13m - 10 = 8 + 8m

13m = 18 + 8m

5m = 18

m = 3.6

User Joel Dean
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.